Reson SeaBat 8125 backscatter data as a tool for seabed characterization (Central Mediterranean, Southern Italy): Results from different processing approaches - Innangi, S.; Barra, M.; Di Martino, G.; Parnum, Iain; Tonielli, R.; Mazzoli, S. (Elsevier, 2015)
Acoustic methods for seafloor mapping have been widely developed over the last decades. In particular, the development of swath bathymetry has allowed the creation of detailed maps of seabed topography and acoustic backscatter data; these data have been used to infer sediment and habitat types. In this paper the capability of Multi-Beam Echo Sounder (MBES) system data to distinguish different seabed types in a site in the Tyrrhenian Sea (Mediterranean) is evaluated; dataset used includes bathymetric data and backscatter intensity, with the support of sediment samples and scuba investigations. The Reson SeaBat 8125 MBES system provides bathymetric and backscatter data. The backscatter data are stored both as Sidescan-like data (intensity values produced by an averaging process) and Snippet data (a time-series of intensity values for each beam). The processing of these acoustic data belongs to a relatively new field of research: the aim of this paper is to show two different processing approaches, and discuss the produced output. The mosaic of images from the Sidescan-like and Snippet data are statistically analyzed, in order to highlight the resolution of the Snippet when dealing with acoustic facies and the correlation existing between granulometric features and the recognized facies. In conclusion, even if no signal appears to be better than the other, it is evident that both Sidescan-like and Snippet data are complementary to a correct interpretation of the seafloor features and can produce a highly detailed acoustic mosaic useful for several scientific areas, including habitat mapping.